Information and Communication Technology as A Requirement for Successful Implementation of Education Managerial Functions - Nikolaevich, Gridnev Anatoly (Lembaga KITA, 2022)
Working with information plays an important role in the management of any educational institution. The Deputy Director in carrying out information and analysis activities must process large amounts of material. The use of information technology helps make this job easier. This article describes the project on the use of information and communication technologies in the management of additional educational organizations for children and analyzes the main directions of informatization in the management of educational institutions. The effectiveness of the use of information technology in managerial activities based on the use of computer technology has been revealed. Managerial activities of the head include processing a large amount of information. For this information to really help make the right management decisions, it must be objective, arrive on time, and reflect the dynamics of change in management objects. In addition, we need technology that managers can use to process this information quickly and accurately, with minimal effort and time. However, in practice, a number of contradictions are revealed; between the need for computerized management of additional education centers and the ability of educational institutions the development management information systems; between the need to build a computerized management process based on scientific systems and their actual implementation through the development of individual areas - the constituent elements of the system (technical equipment, software, training, etc.), between the need to organize management using new information technologies and the level of training of teaching staff that is not adequate for working with modern software. The object of the study is ICT in the management activities of the leadership of an educational institution. The subject of the work is the process of informing the management of educational institutions. The aim of this work is to develop a variant of the management of educational institutions based on the use of information and communication technologies. This method of work. During the study, a complex of different methods was used: the object of research was studied by the method of systems analysis, the method of excluded and included observations, the study of documents governing the management of educational institutions, expert judgments, and sociological surveys. The practical significance of this work lies in the development of the project.